A study on the accessibility measures, services and programs offered by the selected academic libraries in Metro Manila to physically handicapped users - Abrigo, Ryan Joseph M.; Ramos, Marian S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study was conducted to assess the accessibility measures, services and programs of the selected academic libraries in Metro Manila and give necessary recommendations for improvement. Fundamentally, it sought to attain the following: (1) to find out the existing accessibility measures, services and programs offered by the selected academic libraries for their clients with disabilities; (2) to identify certain provisions and guidelines used by the selected academic libraries in providing library and information services to their clients with disabilities; (3) to determine which among the academic libraries have the best accessibility measures, services and programs to offer to physically disabled clients; (4) to formulate appropriate recommendations based on Batas Pambansa Bilang 344, Republic Act 7277 and IFLA Checklist for the enhancement of the accessibility measures and provisions of services and programs in the selected academic libraries. The subjects of this study are chosen based on their experience in handling clients with disabilities.
The data gathered from interviews and ocular inspections revealed that: (1) due to limited number of clients with disabilities, only six academic libraries offer services, specific measures and programs for them; (2) plans of renovating the libraries have been brought up among the academic libraries without accessibility programs to people with disabilities; and (3) certain improvements in libraries' structure and design as well as improvements in the libraries' staff's knowledge in handling clients with disabilities are recognized by the selected academic libraries.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries and the handicapped -- Philippines -- Manila Metropolitan Area; Academic libraries -- Services to people with disabilities -- Philippines -- Manila Metropolitan Area; Academic libraries -- Philippines -- Manila Metropolitan Area